Cell proliferation markers at the invasive tumor front of oral squamous cell carcinoma: comparative analysis in relation to clinicopathological parameters of patients - Aurita Veronica Beovide CORTEGOSO; Natalia Koerich LAUREANO; Alessandra Dutra da SILVA; Chris Krebs DANILEVICZ; Alessandra Sellinger MAGNUSSON; Fernanda VISIOLI; Pantelis Varvaki RADOS
Abstract Objectives To evaluate the number of AgNORs per nucleus and the expression of Ki-67 at the tumor invasion front (TIF) in relation to clinical parameters (TNM), TIF classification and the prognosis of oral squamous cell carcinomas in an Uruguayan population. Material and Methods This study was conducted through a retrospective survey from 2000 to 2010 at the National Institute of Cancer Montevideo, Uruguay and included 40 patients. The samples were obtained from the resection of the tumor and the TIF was defined according with Bryne, et al.5 (1992). Expression of Ki-67 was assessed by the percentage of positive tumor cells and the AgNOR was recorded as the mean AgNOR (mAgNOR) and the percentage of AgNOR per nucleus (pAgNOR). All analyzes were performed by a blinded and calibrated observer. Results No statistically significant association was observed between immunostaining of Ki-67 and AgNOR with the different types of TIF, regional metastasis and patients prognosis, however it was observed an increase in Ki-67 expression associated with worse patient's clinical staging, although not statistically significant. Conclusions Our results suggest that proliferation markers as AgNOR and Ki-67 are not prognostic markers at the tumor invasive front of carcinoma of oral squamous cell.